Penerapan Model Pembelajaran Konstruktivisme Melalui Metode Eksperimen dan Demonstrasi Terhadap Hasil Belajar Siswa pada Materi Fluida - Fartina, Fartina; Hizbi, Tsamarul; Zahara, Laxmi; Sapiruddin, Sapiruddin; Yunus, Muhammad (Universitas Hamzanwadi, 2023)
This study aims to determine whether there is an influence of the constructivism model through experimental and demonstration methods on student learning outcomes on fluid material at SMA Negeri 1 Suralaga in the 2022/2023 academic year